2021
DOI: 10.3389/fonc.2021.749140
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Pancreaticoduodenectomy Versus Conventional Open Approach for Patients With Pancreatic Duct Adenocarcinoma: An Up-to-Date Systematic Review and Meta-Analysis

Abstract: BackgroundTo compare perioperative and oncological outcomes of pancreatic duct adenocarcinoma (PDAC) after laparoscopic versus open pancreaticoduodenectomy (LPD vs. OPD), we performed a meta-analysis of currently available propensity score matching studies and large-scale retrospective cohorts to compare the safety and overall effect of LPD to OPD for patients with PDAC.MethodsA meta-analysis was registered at PROSPERO and the registration number is CRD42021250395. PubMed, Web of Science, EMBASE, Cochrane Cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 26 publications
1
24
0
Order By: Relevance
“…Although LPD had slightly longer operative time than open pancreatoduodenectomy (OPD), [3][4][5] -related meta-analyses showed that LPD was significantly better in hospital stay and intraoperative blood loss for PDAC patients. There were no statistical differences in postoperative pancreatic fistula, postoperative hemorrhage, and perioperative mortality between LPD and OPD for PDAC.…”
Section: In Patients With Pancreatic Head Ductal Adenocarcinomamentioning
confidence: 99%
See 4 more Smart Citations
“…Although LPD had slightly longer operative time than open pancreatoduodenectomy (OPD), [3][4][5] -related meta-analyses showed that LPD was significantly better in hospital stay and intraoperative blood loss for PDAC patients. There were no statistical differences in postoperative pancreatic fistula, postoperative hemorrhage, and perioperative mortality between LPD and OPD for PDAC.…”
Section: In Patients With Pancreatic Head Ductal Adenocarcinomamentioning
confidence: 99%
“…[9] However, no statistical difference was found in overall survival (OS). [4][5][6]10] Chapman et al analyzed data from the NCDB and found that LPD patients aged ≥75 years had significantly longer OS compared with OPD. [8] In addition, after adjusting for patient and tumor-related characteristics, there was a trend toward improved OS in the LPD group.…”
Section: In Patients With Pancreatic Head Ductal Adenocarcinoma What ...mentioning
confidence: 99%
See 3 more Smart Citations